Preparation method of lithium ion battery composite negative electrode and application of lithium ion battery composite negative electrode in lithium battery

By uniformly covering the nano-state inorganic solid electrolyte on the surface of the negative electrode material of lithium-ion battery, the ionic electronic conductive network is constructed, and the lack of performance of the negative electrode material under high-speed charging and discharge and low temperature conditions is solved, and higher electrochemical performance is achieved. Longer cycle life.

CN119447192AActive Publication Date: 2025-02-14INST OF CHEM CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411665574.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-02-14
Estimated Expiration
2044-11-20

AI Technical Summary

Technical Problem

Existing lithium-ion battery anode materials show limited electronic transmission, high lithium-ion battery risk and short cycle life under high-rate charging and discharging conditions.

Method used

The surface of the negative electrode active material is uniformly coated with lithiated nano-state inorganic solid electrolyte by a modified solid phase stirring method to construct an ionic and electronic conductive network in the molten state of low melting point polymer.

Benefits of technology

It improves the rate charging and discharging performance of the negative electrode of lithium-ion batteries, reduces the risk of lithium extraction, extends the cycle life, and improves the safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447192A_ABST
    Figure CN119447192A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a lithium ion battery composite negative electrode and application of the lithium ion battery composite negative electrode in a lithium battery. The composite negative electrode is mainly composed of a negative electrode active material, a low-melting-point polymer, a lithiated nano inorganic solid electrolyte, a conductive additive and a binder. In the preparation process, the surfaces of the negative electrode particles are firstly coated with a layer of polymer, the nano inorganic solid electrolyte is introduced, and the electrolyte shows an ion-electron mixed conductive property after lithiation, so that the ion and electron paths in the negative electrode piece are further improved, the negative electrode polarization is effectively reduced, and the rate capability is improved. Meanwhile, the problem of lithium separation on the surface of the negative electrode in the fast charging and long-cycle process of the lithium secondary battery can be inhibited by utilizing the lower lithium intercalation potential of the solid electrolyte, and the lithiated solid electrolyte can be used as a lithium storage device and continuously releases free lithium ions in the long-cycle process, so that the service life of the lithium ion battery is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of battery electrode materials, and specifically relates to a method for preparing a composite negative electrode of a lithium ion battery and an application of the same in a lithium battery. Background Art

[0002] With the rapid development of new energy vehicles and energy storage industries, the demand for high-performance power lithium batteries continues to grow. The negative electrode has a decisive influence on the energy density, cycle performance, charge and discharge rate, and low-temperature discharge performance of lithium-ion batteries. At present, the negative electrode materials of commercial lithium-ion batteries mainly include carbon-based negative electrodes, silicon-based negative electrodes, lithium titanate, etc. These materials have their own characteristics and advantages, but they also have their own limitations. In addition to the properties of the active material itself, the structure of the negative electrode sheet is also crucial to the performance of the battery. By adding an appropriate amount of conductive additives and binders, an effective electron path can be constructed inside the negative electrode, and the penetration of the electrolyte in the porous electrode can form a good ion path. Under the development requirements of high energy density, thick electrodes with high active material loading and high compaction are an inevitable trend. However, the transmission efficiency of ions and electrons in thick electrodes will be significantly affected. Thick electrodes may lead to limited electron transmission, thereby increasing the charge transfer resistance. This will affect the electrochemical performance of the battery, especially at high rate charge and discharge. At the same time, due to the limitation of electron and ion transmission, the lithium state may be unevenly distributed inside the electrode. This heterogeneity will affect the stability and cycle life of the battery. Therefore, in order to ensure that lithium ions and electrons can quickly pass through thick electrodes, a continuous ion-electron conductive network needs to be constructed.

[0003] In the research and development of negative electrode materials for lithium-ion batteries, coating modification is a very common method. Among them, solid electrolytes are widely used in negative electrode coating due to their high ionic conductivity. Patent CN118507695A proposes a solid electrolyte-coated graphite negative electrode material and its preparation method and application. The report confirms that the solid electrolyte containing Ti has both ionic and electronic conductivity, and coating it on the graphite surface by liquid phase precipitation can improve the rate performance and lithium precipitation problem of graphite materials. However, wet coating often requires post-treatment such as high-temperature sintering, and it is also easy to cause the coating layer to be impure. At the same time, the cost of the wet process is high, and the prospect of industrial application is poor. Dry coating is more practical, but the coating uniformity is difficult to guarantee, which affects the performance of the electrochemical performance of the material, especially the rate performance. Therefore, it is necessary to develop a simple, efficient and economical solid electrolyte coating method to improve the comprehensive electrochemical performance of the negative electrode. Summary of the invention

[0004] In order to improve the electrochemical performance of the negative electrode of lithium-ion batteries, the present invention proposes to coat the surface of the negative electrode active material with a nano-state inorganic solid electrolyte that can be lithiated by a modified solid phase stirring method. First, a layer of low-melting-point polymer is constructed on the surface of the negative electrode material, and the heat generated by mechanical friction during the planetary stirring process is used to melt the polymer on the surface of the negative electrode, thereby enhancing the adsorption of inorganic nano-solid electrolyte particles, thereby obtaining a uniformly coated negative electrode material. The composite negative electrode sheet prepared in this way can form an ion-electron conductive network inside it after lithiation, thereby improving the high-rate charge and discharge performance of the lithium-ion negative electrode. At the same time, since the lithiated solid electrolyte still has lithium storage space, the risk of lithium precipitation of the negative electrode can be reduced, and lithium ions can be continuously released during the cycle to supplement the lack of free lithium ions, thereby improving the safety performance and cycle life of the lithium-ion battery.

[0005] A method for preparing a composite negative electrode for a lithium ion battery comprises the following steps:

[0006] (S1) adding the negative electrode active material to a polymer solution having a melting point lower than 180° C., and stirring until the solvent is completely evaporated to obtain a negative electrode active material having a surface coated with the polymer;

[0007] (S2) mixing the negative electrode active material with the surface coated with the polymer with the nano inorganic solid electrolyte that can be lithiated, and obtaining the negative electrode material uniformly coated with the solid electrolyte after planetary stirring;

[0008] (S3) preparing a slurry of the negative electrode material uniformly coated with the solid electrolyte, a binder, a conductive additive, and a solvent, coating the slurry on a current collector, and drying the obtained negative electrode sheet;

[0009] (S4) The prepared negative electrode plate is lithiated to reduce and lithiate the solid electrolyte, thereby obtaining a lithium-ion battery composite negative electrode product.

[0010] Furthermore, in step (S1), the polymer having a melting point lower than 180° C. is selected from one or more of polyacrylic acid, polyvinylidene fluoride, polyethylene oxide, and polyacrylonitrile; and the concentration of the polymer solution is 0.1 to 0.5 mol / L.

[0011] Furthermore, in step (S1), the amount of the low melting point polymer added is 0.2-1wt% of the mass of the negative electrode active material, preferably 0.5-1wt%; the negative electrode active material is one or a composite of artificial graphite, natural graphite, silicon dioxide, silicon, etc.

[0012] Furthermore, in step (S2), the inorganic solid electrolyte material is a lithium ion conductor material that can react with metallic lithium, and is further preferably one or more of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, and lithium titanium oxide; the particle size of the inorganic solid electrolyte is 5 to 100 nm, preferably 10 to 50 nm.

[0013] Furthermore, in step (S2), the amount of the solid electrolyte is 1 to 5 wt %, preferably 2 to 4 wt %, of the negative electrode active material having a surface coated polymer.

[0014] Furthermore, in step (S2), the speed of the planetary stirring is 2000-3000 rpm; the time of the planetary stirring is 1-2 hours; the ball-to-material ratio used in the planetary stirring is 10-20:1. The speed of the planetary stirring cannot be too low, otherwise the heat generated may not reach the melting point of the polymer, and the purpose of the polymer melting and uniformly coating the negative electrode material cannot be achieved; the speed of the planetary stirring cannot be too high, otherwise the surface and bulk structure of the negative electrode material will be damaged.

[0015] Furthermore, in step (S3), the binder is selected from at least one of PVDF, CMC, and PAA; the conductive additive is selected from at least one of acetylene black, Super P, and carbon tubes; the solvent is selected from at least one of water, N-methylpyrrolidone, and N,N-dimethylformamide. The mass ratio of the negative electrode material uniformly coated with the solid electrolyte, the binder, and the conductive additive is 80-95:2-10:2-10; the amount of the solvent is such that the solid content of the slurry is 25-30wt%.

[0016] Furthermore, in step (S4), the lithiation method described in the step is electrochemical pre-lithiation or chemical pre-lithiation; electrochemical pre-lithiation is achieved by loading lithium supplement additives during the battery assembly process and completing activation during the battery formation process. The lithium supplement additives can be selected from common positive and negative electrode lithium supplement materials; chemical pre-lithiation is mainly achieved by soaking in a polycyclic aromatic hydrocarbon lithium solution.

[0017] Furthermore, in step (S4), in the electrochemical pre-lithiation, the lithium supplement additive is selected from at least one of lithium foil and lithium powder, and the amount of the lithium supplement additive is 2-5% of the designed capacity of the negative electrode; in the chemical pre-lithiation, the polycyclic aromatic hydrocarbon lithium is selected from at least one of naphthyl lithium and biphenyl lithium, the concentration of the polycyclic aromatic hydrocarbon lithium solution is 1 mol / L, and the solvent is selected from at least one of tetrahydrofuran, ethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.

[0018] The present invention also provides a lithium secondary battery, comprising a lithium ion battery composite negative electrode prepared by the above preparation method.

[0019] The present invention realizes uniform coating of the solid electrolyte on the surface of the negative electrode material in a simple and efficient manner through a modified solid phase method, further expanding the new application of inorganic solid electrolytes in the negative electrode of lithium batteries, and utilizing the ionic and electronic mixed conductive properties of its lithiated product to effectively reduce the charge transfer resistance of the negative electrode, thereby greatly improving the comprehensive electrochemical performance of the negative electrode of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 SEM image of graphite surface coated with LATP in Example 1;

[0021] Figure 2 SEM image of graphite surface coated with LATP in Comparative Example 1;

[0022] Figure 3 SEM image of graphite surface coated with LATP in Comparative Example 2;

[0023] Figure 4 Comparison of 4C charging-0.1C discharging curves of lithium-ion batteries in Example 1 and Comparative Example 2;

[0024] Figure 5 Comparison of the cycle performance of the lithium-ion batteries in Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0025] The present invention will be further described below in conjunction with specific embodiments.

[0026] The experimental methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described can be obtained from commercial sources.

[0027] Example 1

[0028] (I) Preparation of composite graphite negative electrode sheet

[0029] (S1) dissolving 0.5 wt% (calculated based on the mass of graphite) polyethylene oxide (PEO, melting point about 65° C.) in deionized water to obtain a polymer solution with a mass concentration of 0.1 mol / L, adding graphite powder to the polymer solution, heating and stirring until the solvent is completely evaporated, to obtain a negative electrode active material with a surface coated with the polymer;

[0030] (S2) The surface-coated polymer negative electrode active material is mixed with Li 1.4 Al 0.4 Ti 1.6 (PO 4 ) 3 (LATP) were mixed in a mass ratio of 98:2 and planetary stirred at 2000 rpm for 2 hours to obtain LATP-coated graphite powder;

[0031] (S3) mixing LATP-coated graphite powder, Super P, and PAA in a mass ratio of 93:2:5 in a deionized water solvent to prepare a slurry with a solid content of 25 wt%, applying the obtained slurry on a copper foil, drying at 60° C. for 12 hours, and then cutting into 10 mm discs to obtain a graphite negative electrode sheet;

[0032] (S4) In a glove box, the graphite negative electrode sheet is brought into contact with a metal lithium foil, and a small amount of electrolyte is added to promote its lithiation. After reacting for 10 hours, the excess metal lithium is removed, and the composite graphite negative electrode sheet is obtained after washing and drying with a dimethyl carbonate solvent.

[0033] (II) Lithium secondary battery assembly

[0034] In an argon atmosphere glove box, the composite graphite negative electrode sheet obtained in (a) and the lithium iron phosphate positive electrode sheet were assembled into a 2032 button battery with an N / P ratio of 1.05 for testing. The electrolyte used was: 1 mol / L lithium hexafluorophosphate (LiPF 6 ) was dissolved in EC / DEC / DMC (volume ratio 1:1:1), the addition amount was 50 μL, and the membrane used was Celgard's PP / PE / PP membrane.

[0035] (III) Performance test

[0036] (3.1) Rate performance test: The obtained battery was subjected to charge and discharge tests at different rates on a blue battery tester. The voltage range was set to 2.5-4.2 V, the charging rates were 0.1C, 0.2C, 0.5C, 1C, 2C, 4C (1C = 170 mAh / g), and the discharge was 0.1C. At each rate, the battery was cycled 5 times in the order of charging first and then discharging.

[0037] (3.2) Cycle performance test: The obtained battery was subjected to constant current charge and discharge cycle test on a blue battery tester. The voltage range was set to 2.5-4.2 V. The battery was first cycled at 0.1 C for 3 cycles and then cycled at 1 C for 100 cycles.

[0038] Example 2

[0039] The other conditions are the same as those in Example 1, except that:

[0040] In step (S1), the amount of PEO added was changed to 0.2 wt % of the graphite powder.

[0041] Example 3

[0042] The other conditions are the same as those in Example 1, except that:

[0043] In step (S1), the amount of PEO added was changed to 1 wt % of the graphite powder.

[0044] Example 4

[0045] The other conditions are the same as those in Example 1, except that:

[0046] In step (S1), PEO is changed to an equal mass of polyacrylic acid (PAA).

[0047] Example 5

[0048] The other conditions are the same as those in Example 1, except that:

[0049] In step (S2), the mass ratio of graphite to LATP is changed to 99:1.

[0050] Example 6

[0051] The other conditions are the same as those in Example 1, except that:

[0052] In step (S2), the mass ratio of graphite to LATP is changed to 95:5.

[0053] Example 7

[0054] The other conditions are the same as those in Example 1, except that:

[0055] In step (S2), LATP is replaced by lithium titanate Li 4 Ti 5 O 12 (LTO).

[0056] Example 8

[0057] The other conditions are the same as those in Example 1, except that:

[0058] In step (S2), the LATP particle size was changed to 50 nm.

[0059] Example 9

[0060] The other conditions are the same as those in Example 1, except that:

[0061] In step (S2), the planetary stirring speed was changed to 3000 rpm.

[0062] Example 10

[0063] The other conditions are the same as those in Example 1, except that:

[0064] In step (S2), the planetary stirring speed was changed to 1500 rpm.

[0065] Embodiment 11

[0066] The other conditions are the same as those in Example 1, except that:

[0067] In step (S2), the planetary stirring speed was changed to 5000 rpm.

[0068] Comparative Example 1

[0069] The other conditions are the same as those in Example 1, except that:

[0070] Step (S1) is eliminated, that is, the graphite is not treated with the polymer solution, and the graphite powder and the LATP powder are directly planetarily stirred.

[0071] Comparative Example 2

[0072] The steps of assembling and testing the performance of the lithium secondary battery are the same as those in Example 1, except that step (I) is changed to the following:

[0073] Lithium hydroxide, aluminum nitrate nonahydrate, tetrabutyl titanate, and ammonium dihydrogen phosphate were added to ethanol in a molar ratio of 1.4:0.4:1.6:3 and stirred evenly. Graphite powder was added in a ratio of 1:1 to 1. 1.4 Al 0.4 Ti 1.6 (PO 4 ) 3 (LATP) was added into the solution in a mass ratio of 98:2, and the solvent was evaporated after stirring at 80°C for 2h to obtain graphite powder coated with LATP precursor, which was heated in argon at 650°C for 4h to obtain 2wt% LATP-coated graphite negative electrode material.

[0074] The electrochemical performance of the lithium-ion battery assembled from the negative electrodes of the above-mentioned embodiment and comparative example was tested, and the results are shown in Table 1 below.

[0075] Table 1 Experimental conditions and corresponding electrochemical performance

[0076]

[0077]

[0078] It can be seen from the above examples that the present invention can improve the electrochemical performance of the negative electrode by coating the inorganic solid electrolyte on the surface of the negative electrode material of the lithium-ion battery and after lithiation, and achieve the capacity improvement and cycle stability of the lithium secondary battery at high rate by adjusting the solid electrolyte material and particle size, coating method, coating amount, activation method and other conditions. From the data in Table 1, the following rules can be obtained:

[0079] 1) After pre-coating the graphite surface with polymer, uniform coating of solid electrolyte can be obtained by mechanical stirring ( Figure 1 ), compared with Comparative Example 1, direct solid-phase stirring of graphite without pretreatment and LATP easily leads to uneven dispersion of LATP ( Figure 2 ), which shows that by pre-building a layer of low melting point polymer, the molten state of the polymer in planetary stirring can be used to more evenly adsorb LATP nanoparticles, thereby forming a more uniform solid electrolyte coating layer, further improving the electrochemical performance of the negative electrode. Compared with Comparative Example 2, the LATP distribution on the graphite surface coated by wet precipitation is uneven ( Figure 3 ), which is due to the fact that the precipitation process of metal ions is not completely controllable and is greatly affected by the surface properties of graphite. This shows that the modified dry coating can effectively regulate the surface properties of graphite and achieve more uniform LATP coating.

[0080] 2) After coating the graphite surface with LATP, the kinetic performance of the negative electrode is improved. In Example 1, the discharge capacity of the lithium iron phosphate / graphite full battery at 0.1C under 4C charging is increased to 131 mAh / g ( Figure 4 ). This is because the lithiated nano-inorganic solid electrolyte builds a better ion-electron conductive network in the negative electrode, reduces the charge transfer impedance, thereby inhibiting lithium precipitation and exerting a higher capacity.

[0081] 3) The cycle stability of the full battery assembled with activated LATP coated graphite anode is also improved, such as Figure 5 As shown, the capacity retention rate of the full battery of Example 1 after 100 cycles at 1C rate is 95.9%. This is because the lithiated inorganic solid electrolyte can act as a lithium storage device. During the full battery cycle, as the polarization increases and the negative electrode potential increases, the lithium in the solid electrolyte is slowly released to supplement the lost free lithium ions, thereby improving the cycle stability.

[0082] 4) By comparing the results of Examples 1, 2 and 3, it can be seen that the rate performance and cycle stability of the lithium secondary battery first increase and then decrease with the increase of the amount of PEO added. This is because too little PEO cannot completely cover the graphite surface, resulting in uneven subsequent LATP coating. Too much PEO will reduce the proportion of negative electrode active materials, and will also affect the charge transfer on the graphite surface, resulting in a decrease in the actual capacity of the negative electrode.

[0083] 5) By comparing the results of Examples 1 and 4, it can be seen that compared with PAA, the rate performance and cycle stability of the lithium secondary battery assembled after PEO-treated graphite coating are better. This is because PEO has a lower melting point and a better mechanical melting effect, which can promote the formation of a more uniform LATP coating effect.

[0084] 6) By comparing the results of Examples 1, 5 and 6, it can be seen that the rate performance and cycle stability of the lithium secondary battery first increase and then decrease with the increase of the LATP coating amount. This is because the LATP particle size is too small to form an effective three-dimensional ion / electron conductive network, and too much LATP will reduce the proportion of negative electrode active materials, resulting in a decrease in the actual capacity of the negative electrode.

[0085] 6) Comparing the results of Examples 1, 9, 10, and 11, it can be seen that the planetary stirring speed should be moderate. If it is too high or too low, the electrochemical performance of the composite negative electrode material cannot be repeatedly exerted. If the speed is too low, the polymer melting point may not be reached, or the coating effect is not good; if the speed is too high, the structure of the negative electrode active material will be destroyed to a certain extent, resulting in a decrease in capacity and cycle performance.

[0086] 8) Comparing Examples 1 and 7, coating LATP and LTO on the graphite surface can improve the rate performance and cycle stability of lithium secondary batteries. Compared with LTO, LATP coating has the best improvement effect. This is because LATP has a higher ionic conductivity, and the electronic conductivity of the product after lithiation is higher, and it can induce the formation of a more stable negative electrode interface layer.

[0087] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a composite negative electrode for a lithium ion battery, characterized in that: The following steps are involved: (S1) adding the negative electrode active material to a polymer solution having a melting point lower than 180° C., and stirring until the solvent is completely evaporated to obtain a negative electrode active material having a surface coated with the polymer; (S2) mixing the negative electrode active material with the surface coated with the polymer with the nano inorganic solid electrolyte that can be lithiated, and obtaining the negative electrode material uniformly coated with the solid electrolyte after planetary stirring; (S3) preparing a slurry of the negative electrode material uniformly coated with the solid electrolyte, a binder, a conductive additive, and a solvent, coating the slurry on a current collector, and drying the obtained negative electrode sheet; (S4) The prepared negative electrode plate is lithiated to reduce and lithiate the solid electrolyte, thereby obtaining a lithium-ion battery composite negative electrode product.

2. The preparation method according to claim 1, characterized in that: In step (S1), the polymer having a melting point lower than 180° C. is selected from one or more of polyacrylic acid, polyvinylidene fluoride, polyethylene oxide, and polyacrylonitrile; and the concentration of the polymer solution is 0.1 to 0.5 mol / L.

3. The preparation method according to claim 1, characterized in that: In step (S1), the addition amount of the low melting point polymer accounts for 0.2-1wt% of the mass of the negative electrode active material, preferably 0.5-1wt%; the negative electrode active material is one or a composite of artificial graphite, natural graphite, silicon dioxide, silicon, etc.

4. The preparation method according to claim 1, characterized in that: In step (S2), the inorganic solid electrolyte material is a lithium ion conductor material that can react with metallic lithium, preferably one or more of lithium aluminum titanium phosphate, lithium aluminum germanium phosphate, and lithium titanium oxide; the particle size of the inorganic solid electrolyte is 5 to 100 nm, preferably 10 to 50 nm.

5. The preparation method according to claim 1, characterized in that: In step (S2), the amount of the solid electrolyte is 1 to 5 wt %, preferably 2 to 4 wt %, of the negative electrode active material with the surface coated with the polymer.

6. The preparation method according to claim 1, characterized in that: In step (S2), the rotation speed of the planetary stirring is 2000-3000 rpm; the time of the planetary stirring is 1-2 hours; and the ball-to-material ratio used in the planetary stirring is 10-20:

1.

7. The preparation method according to claim 1, characterized in that: In step (S3), the binder is selected from at least one of PVDF, CMC, and PAA; the conductive additive is selected from at least one of acetylene black, Super P, and carbon nanotubes; the solvent is selected from at least one of water, N-methylpyrrolidone, and N,N-dimethylformamide; preferably, the mass ratio of the negative electrode material uniformly coated with the solid electrolyte, the binder, and the conductive additive is 80-95:2-10:2-10; the amount of the solvent is such that the solid content of the slurry is 25-30wt%.

8. The preparation method according to claim 1, characterized in that: In step (S4), the lithiation method described in the step is electrochemical pre-lithiation or chemical pre-lithiation; electrochemical pre-lithiation is achieved by loading lithium replenishing additives during the battery assembly process and completing activation during the battery formation process; the lithium replenishing additives can use common positive and negative electrode lithium replenishing agent materials; chemical pre-lithiation is mainly achieved by immersion in a polycyclic aromatic hydrocarbon lithium solution.

9. The preparation method according to claim 8, characterized in that: In step (S4), in the electrochemical pre-lithiation, the lithium supplement additive is selected from at least one of lithium foil and lithium powder, and the amount of the lithium supplement additive is 2-5% of the designed capacity of the negative electrode; in the chemical pre-lithiation, the polycyclic aromatic hydrocarbon lithium is selected from at least one of naphthyl lithium and biphenyl lithium, the concentration of the polycyclic aromatic hydrocarbon lithium solution is 1 mol / L, and the solvent is selected from at least one of tetrahydrofuran, ethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether.

10. A lithium secondary battery, comprising a lithium ion battery composite negative electrode prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Graphite negative electrode material coated with solid electrolyte and preparation method and application of graphite negative electrode material

    CN118507695A

  • Negative electrode composite material, negative electrode pole piece, all-solid-state battery and preparation method

    CN118352510A

  • High polymer electrolyte secondary battery

    JP1999111266A

  • Negative electrode plate for lithium battery, and preparation method and application of negative electrode plate

    WO2023174299A1